The Effect of Diferentiation, Price, and Facility on Customers’ Satisfaction (Case Study on Goen Authentic In East Jakarta) - Mariam, Siti; Panji Kresna, Egi; Haeba Ramli, Abdul (Majalah Ilmiah Bijak, 2022)
This study aimed to analyze “The Effect of Differentiation, Price and Facilities on Consumer Satisfaction (Case Study on Goen Authentic East Jakarta). The research method was quantitative using purposive sampling, with a sample of 35 respondents. The results of this study indicated that (1) the differentiation variable (X1) had    a partially significant effect on consumer satisfaction with a t count of 2,538 and a signification level of 0,016, which was less than 0,05, therefore differentiation (X1) had a significant effect on consumer satisfaction (Y) (2) the price variable (X2) had a t-count result of 0.527 with a signification level of 0,602, which was greater than 0,05, therefore the price (X2) did not significantly affect consumer satisfaction (Y) (3) The facilities had a result of 3,041 with a signification level of 0,005, which was less than 0,05, therefore the facility (X3) had a significant effect on consumer satisfaction (Y) (4) differentiation (X1) Price (X2) and facilities (X3) on consumer satisfaction (Y) obtained F count of 12,57 and a signification level of 0,000, which was less than 0,05, therefore from the regression model it can be concluded that differentiation, price and facilities together affect consumer satisfaction at Goen Authentic.